'n Seisoen in die paradys by Breyten Breytenbach and its translation, a season in paradise by Rike Vaughan. a descriptive approach focusing on the transfer of meaning in the text. - Koopman, William (My University, 1995)
This case study investigates and analyses the transfer of the socio-political elements of meaning, in the translated text, A Season in Paradise (1985). The study attempts to discover and account for any factors which may have impacted on the transfer of the socio-political elements from the source text. to make the study as systematic and as objective as possible, an adaptation of the model of analysis proposed by Lambert and Van Gorp is used. Lambert and Van Gorp are theorists who fall within the branch of translation studies called Descriptive Translation studies. The adaptation of the Lambert and Van Gorp model takes into account the factors which could have influenced the translator's reading of the literary text and which could have impacted on her translation strategy. The macro-analysis establishes the background to the translation and compares the physical features and the publishing circumstances of the target text with that of the source text. It contains a discussion on any similarities or differences found. On the micro-level, specific extracts with a socio-political theme are compared using selected linguistic concepts from Halliday's An Introduction to Functional Grammar as interpretive tools. The shifts discovered here were linked to the discoveries made in the macro-level analysis. It: was determined that prevalent reading strategies at the time did to a limited extent influence the transfer of the socio-political elements of meaning present in the text. This study is done to shed more light on the process of translating a literary work and the factors which may influence this process.
A Translation project submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements of the degree of Master of Arts (Translation).
Keywords: Breytenbach, Breyten -- Translations.; Afrikaans literature -- Translations into English -- Criticism, Textual.; Translations.; Breytenbach, Breyten. 'N Seisoen In Die Paradys.; English literature -- Criticism, Textual.